Anatomical Markers Associated With the Presence of Intracranial Aneurysms in Individuals Screened for Aneurysms - Iris N. Vos; Rick J. van Tuijl; Liselore A. Mensing; Maud E. H. Ophelders; Mireille R. E. Velthuis; Nicolaas P. A. Zuithoff; Gabriel J. E. Rinkel; Hugo J. Kuijf; Jaco J. M. Zwanenburg; Irene C. van der Schaaf; Birgitta K. Velthuis; Ynte M. Ruigrok (Stroke: Vascular and Interventional Neurology)
Background Hemodynamic stress is linked to the development of intracranial aneurysms (IAs) and may be influenced by anatomic variation of intracranial arteries. We assessed diameters and bifurcation angles of intracranial arteries forming the circle of Willis in a cohort of individuals screened for the presence of IAs. Methods Individuals with and without IAs identified at screening with magnetic resonance angiography were compared. Diameters and bifurcation angles of the following arteries were measured using semiautomatic methods: A1 and A2 segments of the anterior cerebral artery, M1 and M2 segments of the middle cerebral artery, P1 segments of the posterior cerebral artery, posterior communicating artery (Pcom), internal carotid artery, vertebral artery, and basilar artery. We employed univariate general linear models to assess group differences. This included subgroup comparisons between individuals with IAs at specific locations and matched controls, and comparisons on group level between individuals with and without IAs, corrected for age and sex. Results In 94 of the 1049 individuals (9.0%) included, IAs were detected. Individuals with middle cerebral artery IAs had wider ipsilateral M2–M2 bifurcation angles compared with controls (121±25° versus 97±19°; P<0.01). Individuals with anterior communicating artery IAs showed smaller angles for the A1–A2 bifurcation (106±16° versus 120±17°; P = 0.02), while those with Pcom IAs had wider Pcom–C7 bifurcation angles (147±14° versus 127±17°; P = 0.02) and smaller diameters below the ipsilateral internal carotid artery top (2.86±0.36 mm versus 3.10±0.33 mm; P = 0.03) compared with controls. Conclusion We found associations between wider M2–M2 bifurcation angles or narrower A1–A2 bifurcation angles and IA presence, consistent with prior literature. Moreover, we uncovered previously unexplored associations, including wider Pcom–C7 bifurcation angles and smaller internal carotid artery diameters in individuals with Pcom IAs. Future research should explore the potential of these markers in predicting IAs in at‐risk populations during follow‐up screenings.